Metabolomics profiling of AKT/c-Met-induced hepatocellular carcinogenesis and the inhibitory effect of Cucurbitacin B in mice - Ji, Xiangyu; Chen, Xin; Sheng, Lei; Deng, Dongjie; Wang, Qi; Meng, Yan; Qiu, Zhenpeng; Zhang, Baohui; Zheng, Guohua; Hu, Junjie (Frontiers in Pharmacology, 2022)
Hepatocellular carcinoma (HCC), the most common kind of liver cancer, accounts for the majority of liver cancer diagnoses and fatalities. Clinical aggressiveness, resistance to traditional therapy, and a high mortality rate are all features of this disease. Our previous studies have shown that co-activation of AKT and c-Met induces HCC development, which is the malignant biological feature of human HCC. Cucurbitacin B (CuB), a naturally occurring tetracyclic triterpenoid compound with potential antitumor activity. However, the metabolic mechanism of AKT/c-Met-induced Hepatocellular Carcinogenesis and CuB in HCC remains unclear. In this study, we established an HCC mouse model by hydrodynamically transfecting active AKT and c-Met proto-oncogenes. Based on the results of hematoxylin-eosin (H&E), oil red O (ORO) staining, and immunohistochemistry (IHC), HCC progression was divided into two stages: the early stage of HCC (3 weeks after AKT/c-Met injection) and the formative stage of HCC (6 weeks after AKT/c-Met injection), and the therapeutic effect of CuB was evaluated. Through UPLC-Q-TOF-MS/MS metabolomics, a total of 26 distinct metabolites were found in the early stage of HCC for serum samples, while in the formative stage of HCC, 36 distinct metabolites were found in serum samples, and 13 different metabolites were detected in liver samples. 28 metabolites in serum samples and 9 in live samples were affected by CuB administration. Additionally, metabolic pathways and western blotting analysis revealed that CuB influences lipid metabolism, amino acid metabolism, and glucose metabolism by altering the AKT/mTORC1 signaling pathway, hence decreasing tumor progression. This study provides a metabolic basis for the early diagnosis, therapy, and prognosis of HCC and the clinical application of CuB in HCC.